2007
DOI: 10.1086/518852
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Aspergillosis in the Intensive Care Unit

Abstract: Data regarding the incidence of invasive aspergillosis (IA) in the intensive care unit (ICU) are scarce, and the incidence varies. An incidence of 5.8% in a medical ICU has been reported. The majority of patients did not have a hematological malignancy, and conditions such as chronic obstructive pulmonary disease and liver failure became recognized as risk factors. Diagnosis of IA remains difficult. Mechanical ventilation makes it difficult to interpret clinical signs, and radiological diagnoses are clouded by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
224
4
18

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 315 publications
(252 citation statements)
references
References 71 publications
6
224
4
18
Order By: Relevance
“…This rate is in line with data of previous studies (24). Out of 36 cases of our ICU patients who met criteria for Aspergillus infection, 36.1% showed IA.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This rate is in line with data of previous studies (24). Out of 36 cases of our ICU patients who met criteria for Aspergillus infection, 36.1% showed IA.…”
Section: Discussionsupporting
confidence: 93%
“…Recent investigations have shown that IA must be considered as an emerging and mortal infectious disease in ICU patients even in the absence of an apparent predisposing immunodeficiency (24,25). In addition, several new publications have also indicated that frequency of IA in the ICU has increased (13,27,30).…”
Section: Introductionmentioning
confidence: 99%
“…Ayrıca daha önce yapılan klinik çalışmalar dikkate alınarak, geniş spektrumlu antibiyotik tedavisine yanıt alınamayan, diğer etiyolojik nedenlerle açıkla-namayan pnömoni ve kötüleşen PA akciğer grafi si bulguları da klinik/radyolojik kriterler olarak kabul edildi 4,5,17 . Öncelikle serum GM pozitifl iği ve BAL örneklerindeki kültür pozitifl iği mikolojik kriterler olarak belirlendi.…”
Section: İpa Olgu Tanımlarıunclassified
“…Ancak immün baskılanması olmayan yoğun bakım (YB) hastalarında da invazif pulmoner aspergilloz (İPA) artan sıklıkta bildirilmekte olup insidansı %0.33-19 arasında değişkenlik göstermek-tedir 4 . Nötropenik olmayan YB hastalarında kronik obstrüktif akciğer hastalığının (KOAH) varlığı, steroid kullanımı, çoklu organ yetmezliği, yoğun bakım ve hastane yatış süresin-deki uzama İPA gelişimini kolaylaştırmaktadır [5][6][7] .…”
Section: Introductionunclassified
“…[1][2][3][4][5][6][7] Of concern, the incidence of invasive fungal infections has been increasing, along with an epidemiologic shift. 4,[6][7][8] Although Candida spp.…”
mentioning
confidence: 99%